Evaluation of screening for hypertension in general practice with an automatic machine. Issue 6405 (26th November 1983) - Stephens, W P; Tunbridge, R D; Moss, D A
Abstract : An automatic device for measuring blood pressure was used to screen all patients aged 30 to 65 years registered at a health centre. Of those who were eligible, 55% attended. Patients with previously recognised hypertension were more common among the attenders than among the non-attenders. High readings obtained on the automatic device possibly deterred some patients from reattending for follow up measurements of blood pressure. Although the device is quick and easy to use, the logistic challenge of formal blood pressure screening is considerable. Hypertension was discovered in 52 patients (mean diastolic pressure greater than 100 mm Hg). Retrospective analysis of their medical records showed that a third had had an abnormal blood pressure reading noted during the past 10 years and no further action had been taken, and almost three quarters had attended their practitioner during the previous year without having a blood pressure measurement recorded. One year after the screening procedure two fifths of the newly discovered hypertensive patients had defaulted from follow up and treatment. Automatic devices are not a short cut to the discovery of occult hypertension. Case finding by routine measurement of blood pressure at surgery visits is more efficient.